Interpretation of Overly Open Advertising Texts in Print Media - CHEN, YUCHI (2011)
The advertising texts of print media is one of the important manner to communicate the marketing messages with consumers. Under the post modern era, the form of advertising texts has been influenced by the reading habit of readers. Overly open advertising texts which is anti-formed, irrational appealing, image centred and ambiguous, is popular for marketers to transmitting their product and brand information. However, whether the overly open advertising texts is interpreted by consumers, to what extent consumers are going to involved in the advertising texts and the attitude differences of consumers. In this research, the examination of interpretation strategy toward overly open advertising texts is targeting on the consumers with Western and Eastern cultural background. According to Hofstede (2001), the cultural characteristics can be classified distinctly into people from Western and Eastern countries. Also, the three aspects, namely consumer attitude, involvement, and cognitive dissonance, are adopted to provide the thoroughly understand toward overly open advertising texts. In order to gain the understanding of the overly open advertising texts, qualitative research method is employed in this research to gain the in-depth information from both Western and Eastern participants. During the semi-structured interview, advertisements with overly open advertising texts were shown to interpreters to obtain the data from participants. The findings of the study have considerable managerial and theoretical implications, and can represent an starting point for future research into this topic.